Tracking the green transition in the European Union within the framework of EU cohesion policy: Current results and future paths - Lela Tijanić; Ines Kersan-Škabić (Economies, 2025)
Green transition is one of the priority areas in the European Union (EU), and thus also the focus of EU cohesion policy implementation during the 2021-2027 programming period, through 'green growth'. To establish adequate guidelines and achieve better outcomes, it is necessary to observe and evaluate current results connected with these aspects. In terms of the complexity of the green transition domains, measuring green transition is still developing. The aim of this paper is to give an overview of the approaches that can be used in tracking the green transition as a result of EU cohesion policy implementation and to analyse achievements associated with the green transition. This will be done using desk research, previous studies, documents, evaluation reports and secondary data on the financing under the European Structural and Investment Funds (ESIFs) in EU member states, with a special emphasis on themes such as the low-carbon economy, climate change adaptation and risk prevention, environment protection and resource efficiency, and network infrastructure in transport and energy. The paper discusses these results in the context of the current challenges faced by the EU in becoming a leader in the green transition and contributes to the evaluation of the EU cohesion policy.
Keywords: 330; EU cohesion policy; ESIFs; green transition; tracking